FINANCIAL ANALYSIS IN BROILER BREEDERS WITH PARTNERSHIP SYSTEM IN CLOSED HOUSE CAGE (Case Study in The Arcana Broiler Farm, Candikusuma Village, Melaya District, Jembrana Regency) - M., Lumbansiantar; Mahardika, I G.; Sukanata, I W. (Jurnal Peternakan Tropika; Vol 9 No 3 (2021): Vol. 9 No. 3 Tahun 2021; September - December, 2021)
This study to determine the production performance of broiler farms kept in closed house cages.  This research was conducted in a closed house system with a capacity of 12,000 chickens at Arcana Farm located in Candikusuma Village, Melaya District, Jembrana Regency, Bali Province, for 2 months from December 2020 to February 2021. The variables observed in this study are body weight gain, feed consumption, depletion, feed conversion ratio (FCR), performance index (IP), cost, revenue, Revenue Cost Ratio (R/C Ratio), and BEP. The results of this study showed that the average weight of chickens at 33 days of age was 1.790 kg/head, the average body weight gain was 1.754 kg/head, the average ration consumption was 2.696 kg/head, the average FCR value was 1.53 with an R/C ratio of 1, 17, depletion 2.79% and the average performance index of chickens 366,8. Investment costs incurred are Rp. 547.565.000,- total production costs are Rp. 320.059.955/period, the net income of farmers is Rp. 53.597.345/period. This effort reached BEP on the production of 2,261 kg of live chickens or 1,263 chickens and the selling price of chickens was Rp. 14,634/kg live weight.  The results of this study indicate that the broiler farming business that is kept in closed cages with a partnership pattern is good and feasible to do.   Key words: chicken broilers, closed house